Two new Criconemoides species from KwaZulu-Natal wetlands, South Africa (Nematoda: Criconematidae) (Journal of Nematode Morphology and Systematics, 2010)
Two new nematode species belonging to the genus Criconemoides are described from wetlands in Kwazulu- Natal. Criconemoides ixaphozi sp. n. is characterized by having 106-128 retrorse body annuli dorsally, three to six anastomoses and irregularities present along whole length of body demarcating a broken line, true submedian lobes or labial plates are not present on labial area, stylet 40-49 μm long, closed vulva, straight vagina and no projections on anterior vulva lip, and acute tail with small lobes on last one to three annuli; fourth stage juvenile similar to female. Criconemoides zulu sp. n. is distinguished by its body strong ventrally curved, 8-20 anastomoses and stretches of irregularities almost forming a lateral line along the whole length of the body, 138-152 retrorse annuli with rough margins on dorsal side, no true submedian lobes and labial plates, stylet 56.5-63.5 μm long, vulva closed and not projecting beyond the body outline, vagina straight, and rounded tail tip with a few small lobes; fourth stage juvenile similar to female.